Economic Sanctions of EU against Russia - Does it Make Sense? - Mazur, Mykola; Žamberský, Pavel; Coniglio, Nicola; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
In 2014 conflict between Russia and Ukraine has started. It has triggered an imposition of international sanctions against Russia by western countries and the EU. An objective of this research is to evaluate the efficiency of implemented sanctions on the economy of Russian Federation. Economic consequences of bilateral sanctions, which the EU and West applied against Russia in protest at Russian aggressive actions in Crimea and eastern regions of Ukraine, as well as countersanctions (“self-sanctions”), which Russian Federation announced against such countries, will be considered. On the basis of the carried-out analysis forecasts of possible influences of such consequences on the development of Russian economy will be made. European Commission study estimated that sanctions would cost Russia 0.6% of its GDP in 2014, and 1.1% in 2015. The same report put the impact on the EU economy at 0.2% and 0.3% respectively. According to Russian experts, the potential adverse impact of sanctions on the Russian economy is estimated at 8-10% of GDP and that on the EU economy at some 0.5% of GDP. This work will also include prediction of the possible evolution of the GDP of Russian Federation, Russian ruble exchange rate, gold and foreign currency reserves. Predictions will be based on econometric analysis using VAR model.
Vedoucí práce: Pavel Žamberský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses